Strengthening Primary Health Services for Child Nutrition Interventions in Limited Access Area: A Cross-Sectional Study at Seko Health Center - Hikmah B, Nurul; Puspitasari, Ayu; Islamiah, Nurhidayati (An Idea Health Journal, 2025)
Background: One of the government’s policies to address nutritional problems is the strengthening of primary health services through the Integrated Health Service Post (Posyandu) program. This study aims to to analyze the strengthening of primary health services in the implementation of child nutrition interventions in the limited-access area of the Seko Health Center.Method: A quantitative research design with a cross-sectional approach was employed. The study sample consisted of 73 mothers of toddlers, selected using a simple random sampling technique. Data were collected using a structured questionnaire, and bivariate analysis was performed to examine the strengthening of primary health services for child nutrition interventions. The results showed that the variables of tangible evidence, reliability, responsiveness, and empathy collectively influenced the strengthening of nutrition interventions in primary health services, with a coefficient of determination (R²) of 45.9%. Conclusion: Strengthening primary health services requires enhancing the role of health cadres by improving training programs to increase their competence and knowledge—particularly for newly recruited cadres.